PENGEMBANGAN MEDIA AUDIO-VISUAL ANIMASI BERBASIS PROBLEM-BASED LEARNING PADA PEMBELAJARAN IPS KELAS IV SD - Cintya, Cintya Febriyanda Wulandari; Marini, Arita; Imaningtyas, Imaningtyas (Educational Technology Journal, 2023)
This study aims to develop problem-based learning-based audio-visual animation in social studies learning with the theme "My Hero" as a distance learning video for fourth grade elementary school students. Respondents in this study were students of class IV. The development model used is ADDIE with modifications to the implementation stage, with analysis, planning, development, implementation and evaluation stages. Data collection techniques used are observation, interviews, and questionnaires. The recapitulation of problem-based learning audio-visual animation conducted by media experts scored 98.21%, material experts scored 83.33%, and linguists scored 100%. The results of the recapitulation of the test for grade IV students in the one to one stage involved 4 students and 1 class teacher getting a score of 89.5%. Therefore, audio-visual animation based on problem-based learning can be said to be valid and appropriate for use in distance learning for fourth grade elementary school students.